A Possible Mechanism of Zika Virus Associated Microcephaly: Imperative Role of Retinoic Acid Response Element (RARE) Consensus Sequence Repeats in the Viral Genome - Kumar, Ashutosh; Singh, Himanshu N.; Pareek, Vikas; Raza, Khursheed; Dantham, Subrahamanyam; Kumar, Pavan; Mochan, Sankat; Faiq, Muneeb A. (Frontiers in Human Neuroscience, 2016)
Owing to the reports of microcephaly as a consistent outcome in the foetuses of pregnant women infected with ZIKV in Brazil, Zika virus (ZIKV) - microcephaly etiomechanistic relationship has recently been implicated. Researchers, however, are still struggling to establish an embryological basis for this interesting causal handcuff. The present study reveals robust evidence in favour of a plausible ZIKV-microcephaly cause-effect liaison. The rationale is based on: (1) sequence homology between ZIKV genome and the response element of an early neural tube developmental marker ‘retinoic acid’ in human DNA and (2) comprehensive similarities between the details of brain defects in ZIKV-microcephaly and retinoic acid embryopathy. Retinoic acid is considered as the earliest factor for regulating anteroposterior axis of neural tube and positioning of structures in developing brain through retinoic acid response elements (RARE) consensus sequence (5′–AGGTCA–3′) in promoter regions of retinoic acid-dependent genes. We screened genomic sequences of already reported virulent ZIKV strains (including those linked to microcephaly) and other viruses available in National Institute of Health genetic sequence database (GenBank) for the RARE consensus repeats and obtained results strongly bolstering our hypothesis that ZIKV strains associated with microcephaly may act through precipitation of dysregulation in retinoic acid-dependent genes by introducing extra stretches of RARE consensus sequence repeats in the genome of developing brain cells. Additional support to our hypothesis comes from our findings that screening of other viruses for RARE consensus sequence repeats is positive only for those known to display neurotropism and cause foetal brain defects (for which maternal-foetal transmission during developing stage may be required). The numbers of RARE sequence repeats appeared to match with the virulence of screened positive viruses. Although bioinformatic evidence and embryological features are in favour of our hypothesis, additional studies including animal models are warranted to validate our proposition. Such studies are likely to unfold ZIKV-microcephaly association and may help in devising methods to combat it.